A mistagogia de Cirilo de Jerusalém e o eco na catequese pós-Vaticano II - Nascimento, Edvanio de Jesus (2019)
The process of Christian initiation, understood as having an experience with mystery, has been present in the Catholic Church since its beginning and it remains a catechetical orientation in the context of post-Vatican II. This research has, therefore, the objective of establishing the relations and influences of Cyril from Jerusalem’s mistagogical catechesis in the formation of young children, young adults and adults, today. In order to do so, it seeks to delimit an approach between mistagogy and mystery, in the context of primitive Christianity, aiming to understand the intrinsic relation between language and the condition of unconditional Mystery of God. For theoretical support the proposal of authors such as the theologist Paull Tillich, who calls attention to a non-superficial vision of mystery was used, as well as Leonardo Boff, who at proposing a concept of mystery, do it in direct relation to the process of initiation to mysterious religions. Also, as a result of the connection between mystery and language, the value of symbolic dimension was worked out. In the second chapter, it was approached more specifically, the relations between mystagogy and catechesis in the vision of Cyril of Jerusalem. Finally, in the third chapter, it was researched in which ways Cyril of Jerusalem’s mystagogical thought gives basis to the development of mistagogical catechesis after the Second Vatican Council, in the light of some documents of the magisterium that guide the overcoming of the existing catechetical practice for a catechesis of. catechumenal inspiration.